SOFTWARE OF THE CALCULATION OF NORMATIVE MONEY ESTIMATION OF INVESTMENT-ATTRACTIVE LAND PLOT: Array - Tvoroshenko, I.; Trubaieva, S. (Municipal economy of cities (Technical science), 2019)
A three-dimensional model of the land plot of the abandoned children's camp «Dibrova» has been developed, which enables a specialist of the specified subject area with a high degree of reliability to perform an assessment of immovable property, taking into account the necessary information located in the geodatabase. It is established that the normative monetary valuation of land determines the value of land due to its quality. All data for the calculation of normative monetary valuation is normative, defined and established by certain competent authorities. Normative monetary valuation of a certain land plot can be obtained by contacting a specialist of the State Land Cadaster. The software developed during the study allows to independently calculating normative monetary estimation of non-agricultural land plots. Taking into account that expert appraisers who determine the market value of land at the valuation date determine the expert monetary valuation of land, the factors and characteristics of the land plot may increase or decrease the price of this property. The report on the monetary valuation of assets indicates the real market value of the property, in this case, the land plot. The normative monetary assessment of the land plot of the abandoned children's camp «Dibrova» (UAH 6 206 096.23) is significantly different from the expert monetary valuation for expenditures (UAH 2 018 264.21) or the profit method (UAH 2 844 247.14). The normative monetary assessment of the land plot is made for the purpose of the economic incentive for rational use and protection of land, etc. An expert evaluation is carried out in the course of implementation of civil law agreements on land plots, it is more objective, as an expert appraiser may take into account a number of factors that affect the value of land and, in turn, an expert assessment is as close as possible to real market value, unlike the normative monetary valuation.